Until forever - Linn, Michael (Michael A.); Bailey, Stephen Anthony; Lawlor, Madison; Anderson, Jamie (Linn Productions, 2016)
High school sweethearts Michael and Michelle are madly in love with each other and dream about their future together. But when Michael is diagnosed with a rare cancer and confined to a hospital room, their love and faith are tested to the limits. Seeking answers to difficult questions, they begin praying for a miracle that does not seem to be coming. As Michael fights to live, his brother Matt struggles with his own illness: a dark and growing depression. And Michael's unlikely friendship with a fellow hospital patient provokes his own doubts about the value of life.